PENGARUH KEMUDAHAN PENGGUNAAN DAN LITERASI TEKNOLOGI TERHADAP MINAT PENGGUNAAN SURAT PEMBERITAHUAN TAHUNAN ELEKTRONIK DALAM PELAPORAN PAJAK DI YOGYAKARTA - Ratno Ratno (Jurnal Statistika Industri dan Komputasi, 2019)
Abstract. This research aims to determine : (1) the influence of ease of use on the interest in using E SPT application (2) the influence of literacy of technological on the interest in using E SPT application (3) the ease of use and literacy of technological on the interest in using E SPT application. This research includes associative research or relationship by using a quantitative approach. The population in this research are individual taxpayers in Yogyakarta. The technique used in data collection is the prerequisite analysis test, simple and multiple linear regression. The result of this research show that: (1) there is positive influence of ease of use of usefulness towards the interest in using E SPT application, proven by the t count value of 3,368, significance 0,000<0,05 (2) there is negative influence of literacy of technological towards the interest in using E SPT , proven by the t count value of 0,999, significance 0,323>0,05 (3) there is positive influence of perceptions of usability, ease of use and literacy of technological on the interest in using E SPT application, proven by the F value of 13,750, Adjusted R2 0, 424.